Bioelectric activity of the knee joint antagonists in sprinters during running start - Chwala, W.; Ambrozy, T.; Mucha, D.; Mirek, W. (Journal of Kinesiology and Exercise Sciences, 2016)
Purpose: Bioelectric activity of antagonists of the knee is one of the key factors in accelerating sprinters` center of mass in during the first seconds of a race. This significantly determines the final result of the sprint.Basic procedures: The study involved three sprinters from AZS AWF Krakow, members of the national team. The evaluation assessed the bioelectric activity of the rectus femoris and biceps femoris muscles and their share in total employment of both legs during the start between the 3rd and 6th seconds of the run. In addition, maximum activity was assessed in terms of the MVC muscle in isometric contraction. On the basis of the analyzed involvement of mass of both muscles, we measured the sprinters acceleration during the initial seconds of the run, relative to their maximum capacity to generate muscular strength and the asymmetry of bioelectrical activity of the muscles in both legs.Main findings: There has been similar interest in antagonist activity in total employment of the knee joints in both legs and muscle involvement giving a distinct advantage in acceleration of CoM on the side of the dominant right limb. Average values of bioelectrical activity of individual muscles were not significantly different (p<0.05) when monitoring first the 3rd and 6th seconds of the run, which indicates a high degree of fixation patterns of recruiting muscle motor units under the influence of training. During the test, we recorded much higher values in the MVC for the knee extensors.Conclusion: The effective use of the knee joint flexor muscles in accelerating CoM are largely determined by neuromuscular coordination, and to a lesser extent, the maximum potential force. The opposite situation was observed in the group of muscles straightening the knee joints of athletes. They received similar values as in the case of MVC, and their effective use during the run is characterized by distinct asymmetry, indicating the development of the individual athletes bioelectric activity of individual stereotypes.